The effectiveness of the strategy of multiple intelligences in the development of critical thinking and learning in the interpretation of secondary students in the middle class in the city of Baha - Ahmed, Saadia Said (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to identify the effectiveness of using the strategy of solving problems based on multiple intelligences in the development of critical thinking skills and the survival of the effect of learning in the interpretation of the second grade intermediate students. The study was applied according to semi-experimental design. The study population included all second grade students in Al-Baha for the academic year (1438-1439). The sample was randomized to 50 students. The researcher used a measure to measure critical thinking The results of the study proved the effectiveness of a multi-intelligence teaching strategy in the development of critical thinking skills and the survival of the learning effect. There were statistically significant differences at the level of 0.05 بين between the average scores I The experimental group, which was studied using a multi-intelligences-based teaching strategy in developing critical thinking skills and the average score of students in the control group who studied using the traditional education in the post-test of the achievement test, obtained a general mean (47.00) I got it experimental, and the differences in favor of the experimental group. The results showed that there were no statistically significant differences at the mean level of 0.05 بين between the average of the experimental group in the post and post achievement test of critical thinking skills. In conclusion, the study recommended that the theory of multiple intelligences should be included in the educational curriculum in general as it contributes to the improvement of critical thinking skills among students.
Keywords: multiple intelligences; critical thinking; strategy; problem solving